Comparative Effects of Origanum majorana Aqueous Extract and Insulin-Like Growth Factor-1 (IGF-1) on Neurotransmitters, Biochemical, and Enzymatic Parameters in Male Mice Exposed to Zinc Oxide Nanoparticles-Induced Stress. - Dr. Ashwaq Jabbar Almiahy,; Ban Abdulhussein Salih, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Zinc oxide nanoparticles (ZnO NPs) have attracted tremendous attention due to their value use in cosmetics, medicine, food packaging among other industries. At the same time, the rising concern of their possible toxicity, especially their capacity to cause neurotoxicity in biological organisms, is worrisome. insulin-like growth Factor-1 (IGF-1) has been established as a neurotrophic factor that facilitates growth, differentiation, and survival of neurons. However its effectiveness in countering the neurotoxicity caused by zinc oxide nanoparticles (ZnO-NPs) is still unclear. Origanum majorana is claimed as a natural antioxidants herb, which has exhibited strong neoroprotective effects. The aim of this study is to investigate events to compare between Origanum majorana aqueous extract (OMAE) and IGF-1 on neurotransmitters, oxidative stress markers, and enzymatic changes in male mice subjected to stress by ZnO NPs. 40 male Swiss albino mice were randomly divided into four equal groups (n = 10/group): Control Group G1: Untreated, ZnO-NPs Group G2: (50 mg/kg/ intraperetonial) for seven days, ZnO-NPs + IGF-1 Group G3 (100 µg/kg, subcutaneous) for seven days post-ZnO-NP exposure, ZnO-NPs + OMAE Group G4: (200 mg/kg, orally) also for seven days post-ZnO-NP exposure. Results showed that treatment with OMAE and IGF-1 repaired levels of (dopamine, serotonin and norepinephrine), as well as ameliorated the oxidative stress biomarkers (GSH, MDA and TAC) and activities of (SOD, CAT and AChE) enzymes. However treatment with OMAE showed superior potency. In conclusion OMAE demonstrated preferable neuroprotective effects compared to IGF-1 in attenuating ZnO-NP-induced stress. These findings highlight the efficacy of OMAE as a natural therapeutic agent for nanoparticle-induced neurotoxicity.